1991
DOI: 10.1227/00006123-199103000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Hypophysitis with Involvement of the Cavernous Sinus and Hypothalamus

Abstract: Two cases of lymphocytic hypophysitis are reported, in which hypothalamic involvement causing diabetes insipidus was a prominent clinical feature. In one case, a man had clinical and radiological evidence of the involvement of the cavernous sinus. This represents the second reported case of a man with lymphocytic hypophysitis. A transsphenoidal biopsy established the diagnosis in both cases. Neither the involvement of the cavernous sinus nor permanent diabetes insipidus has been reported previously. A review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…41 Therefore, the parasellar T2 dark sign is more suitable for LYH that infiltrates around the pituitary. Some previous studies have reported cavernous involvement in patients with LYH, 5,6,10,[42][43][44][45][46] but no studies have mentioned the parasellar T2 dark sign.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…41 Therefore, the parasellar T2 dark sign is more suitable for LYH that infiltrates around the pituitary. Some previous studies have reported cavernous involvement in patients with LYH, 5,6,10,[42][43][44][45][46] but no studies have mentioned the parasellar T2 dark sign.…”
Section: Discussionmentioning
confidence: 96%
“…The treatment of LYH remains controversial, though conservative management with close clinical observation has been advocated on the basis of its often benign transient course. 9,10 The correct diagnosis of LYH contributes to avoiding needless surgery, which is invasive and sometimes results in endocrine dysfunction. However, distinguishing LYH from pituitary adenomas can be difficult.…”
mentioning
confidence: 99%
“…Chronic inflammation in the sella turcica is classified according to the gland of main involvement. Lymphocytic infiltration confined mainly to the anterior pituitary is termed lymphocytic adenohypophysitis [5,7,[17][18][19], and that confined mainly to the neurohypophysis and inf undibulum is termed infundibuloneurohypophysitis [8]. These hypophyseal inflammatory diseases have been considered to be autoimmune with a self-limiting course [20][21][22][23][24], but some of these diseases have also been found to have associated lesions of adjacent structures [17-19, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery should be performed in cases with progressive compression or those in whom radiological and/or clinical progression occurs during conservative medical management (7). The hyperprolactinemia and mass effect such as visual disruption and stalk compression (DI) resolves after surgery in most cases (23,27,29). On the other hand, definitive histological diagnosis of hypophysitis may obviate the unnecessary use of high-dose steroid therapy and facilitate the treatment of other conditions such as infection or neoplasm (21).…”
Section: Patientmentioning
confidence: 99%